Two different variants of leg repositioning at maximal sprint speed of high performance junior sprinters - Mattes, K.; Wolff, S.; Losekamm, B. (International Journal of Performance Analysis in Sport, 2021)
Two variants of leg repositioning are described biomechanically and examined for differences in step kinematics. Based on leg angle (two-point angle between radius of leg centre of gravity and a horizontal line) during air phase, 30 juniors were divided into two groups (n = 15), large leg angle (LLA, leg angle = 80 ± 4°) and small leg angle (SLA, leg angle = 69 ± 5°). Maximal flying 30-m sprints were recorded (200 fps) and group differences were analysed using a 5-point leg model. With comparable leg length, both groups differed in leg moment of inertia and leg angular velocity. Group SLA reduced knee angle under the body, the thigh of swing leg passed the support leg early, and reached a higher position during knee lift, followed by a higher vertical foot velocity during pre-support. At take-on, both groups achieved a comparable hip, knee and foot angle. Due to higher mass of thigh (66%) compared to lower leg, foot and spikes (34%), thigh movement is essential for repositioning. Despite SLA advantages, three of the six fastest sprinters (v > 10.4 m/s) were evenly divided into both groups. An influence on step length, step frequency, ground contact and flight time was not found.